1999
DOI: 10.3354/meps187251
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid signature analysis from the milk of Antarctic fur seals and Southern elephant seals from South Georgia:implications for diet determination

Abstract: ABSTRACT-Fatty acid signature analysis (FASA) makes use of specific fatty acids, a s well as entire profiles, to study dietary relationships at different trophic levels. Previously, FASA has been used in marine ecosystems in which diet determination by more direct methods is difficult and sometimes rnisleading This study examined fatty acid profiles In milk from 2 species of pinniped from the Southern Ocean that were expected to have highly contrasting diets. Milk samples were collected from Antarctic fur seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 29 publications
1
34
0
1
Order By: Relevance
“…The ability of FA profiles to reflect differences in diet structure depends on the degree of dietary specialization and the magnitude of geographical or temporal separation (Iverson et al 1997b;Brown et al 1999). For differences in diet between seals foraging in different zones to be detected by examining FA profiles, several scale-dependent conditions must be satisfied: (i) prey communities within these putatively distinct ecological zones must be measurably different from each other, with minimal over-lap of prey species among zones; (ii) prey species within each geographical zone must possess distinct FA profiles; and (iii) the combined FA profile of a number of dietary items of the predators from each zone must retain sufficient individuality to allow distinction between the animals that forage in each region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of FA profiles to reflect differences in diet structure depends on the degree of dietary specialization and the magnitude of geographical or temporal separation (Iverson et al 1997b;Brown et al 1999). For differences in diet between seals foraging in different zones to be detected by examining FA profiles, several scale-dependent conditions must be satisfied: (i) prey communities within these putatively distinct ecological zones must be measurably different from each other, with minimal over-lap of prey species among zones; (ii) prey species within each geographical zone must possess distinct FA profiles; and (iii) the combined FA profile of a number of dietary items of the predators from each zone must retain sufficient individuality to allow distinction between the animals that forage in each region.…”
Section: Discussionmentioning
confidence: 99%
“…Different ecological zones in the Southern Ocean are likely to support different prey communities (Knox 1994); wide-ranging species, such as elephant seals, that forage within these different geographical zones should therefore be exploiting different prey. As such, elephant seals are a good test species for the application of FA signature analysis to determine diet structure (Brown et al 1999). If even coarse-scale differences are not detectable, then the approach is unlikely to contribute much to the understanding of the variation in the diet of top predators in this, or other, marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that the increase of 20:1n-9 and 22:1n-11, and the associated decrease in 14:0 and 20:5n-3 levels, was due to an increased consumption of fish in the latter part of the breeding season, which was observed in scats collected from around the breeding beaches. However, Brown et al (1999) were unable to associate milk samples collected from the same population in March of the same year with any fish prey species examined. If the seasonal differences in the current study were caused by increased consumption of fish, then we would have expected 2 things, firstly, that the amount of fish occurring in enemas would increase during the breeding season and, secondly, that milk samples from trips that showed fish predation would have different signatures from those that simply contained krill.…”
Section: Seasonal Differencesmentioning
confidence: 99%
“…Both are specifi c to, and apparently ubiquitous in, marine prey yet are neither stored nor synthesized by higher vertebrates and in mammals are eliminated rapidly from the circulation following ingestion (Edmonds and Francesconi, 1977Yancey et al, 1982;Vahter et al, 1983;Al-Waiz et al, 1987Van Waarde, 1988;Cullen and Reimer, 1989;Brown et al, 1990;Shibata et al, 1992;Smith et al, 1994;Svensson et al, 1994;Zhang et al, 1999;Lehmann et al, 2001). The biomarker method provides information on recent food intake within a timescale of hours to days, in contrast to fatty acid signatures or stable isotopes in fl uids or tissue samples, which integrate food intake over a period of months (Iverson et al, 1997a(Iverson et al, , 1997bBrown et al, 1999).…”
Section: Monitoring Food Consumption During the Lactation Periodmentioning
confidence: 99%